Examining Gendered Experiences in Engineering Workshops - Moison, Elizabeth A. (Tufts University. Tisch Library., 2018)
This project consisted of 10 interviews with young girls who attended the Center for Engineering Education and Outreach (CEEO) summer engineering workshops. Participants ranged in age from 2nd to 7th graders, and were interviewed in the hopes of understanding what their experience as young girls were in those workshops, and how their engineering identity and gender identity informed that experience. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.